2021
DOI: 10.4103/ijo.ijo_1171_21
|View full text |Cite
|
Sign up to set email alerts
|

Immediate impact of COVID-19 on eye banking in India

Abstract: Purpose: In India, COVID-19 infected more than 10 million and caused more than 148,000 fatalities during 2020. Due to “lockdown” eye banks were shuttered in March, 2020 and reopened for operations in the month of May, 2020. This study assesses the immediate impact of the pandemic on eye banking and cornea transplantation in India. Methods: Data was gathered through an online survey of the eye banks and cornea surgeons in India. The questionnaire collected information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In their survey, the least stringent criteria mandated a 14-day symptom-free period before death, whereas the most stringent criteria mandated a period double that time. Moreover, they reported that the definition of COVID-19 symptoms varied among different exclusion guidelines, with the strictest criteria mandating exclusion of those with “unexplained cough, unexplained asthenia and myalgia, intermittent fever, shortness of breath or unexplained conjunctivitis before death.” Such variability in screening criteria was also observed in a survey of Indian eye banks ( 17 ), which reported that a fraction of the eye banks avoided tissue retrieval from COVID-19 positive cases (44.4%) or those with suspicious respiratory symptoms (36.7%). In contrast, some eye banks (16.67%) completely halted tissue collection.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In their survey, the least stringent criteria mandated a 14-day symptom-free period before death, whereas the most stringent criteria mandated a period double that time. Moreover, they reported that the definition of COVID-19 symptoms varied among different exclusion guidelines, with the strictest criteria mandating exclusion of those with “unexplained cough, unexplained asthenia and myalgia, intermittent fever, shortness of breath or unexplained conjunctivitis before death.” Such variability in screening criteria was also observed in a survey of Indian eye banks ( 17 ), which reported that a fraction of the eye banks avoided tissue retrieval from COVID-19 positive cases (44.4%) or those with suspicious respiratory symptoms (36.7%). In contrast, some eye banks (16.67%) completely halted tissue collection.…”
Section: Resultsmentioning
confidence: 71%
“…Due to an increase in the number of wasted donor tissues, Busin et al ( 27 ) underlined the importance of exploring alternative procurement techniques that would extend the storage time of procured corneal tissues and reported tissue dehydration as a useful alternative method, especially in the case of deep anterior lamellar keratoplasties. A survey of eye banks and surgeons in India showed a statistically significant increase in the use of long-term tissue preservation methods in the same period in 2020 compared to previous years ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, COVID also saw an increase of 125.4% in the use of glycerin-preserved corneal tissues, which had reliable therapeutic outcomes. [ 44 ] The pool of eligible donors decreased because patients who had COVID or were suspected positive at the time of death were not eligible for organ donation, despite the lack of evidence demonstrating possible transmission of COVID-19 through corneal transplantation. For organ procurement, the handling and harvesting procedures changed.…”
Section: Covid and Eye Bankingmentioning
confidence: 99%
“…The total number of eye donations in the pre-COVID-19 era was 50,953, which drastically reduced to 18,359: a 63% decline. [ 3 ] Similarly, total corneal transplantation in 2019 was 27,075, which came down to 12,998: a 52% drop. Das et al .…”
mentioning
confidence: 99%